STRATEGI REKAYASA LALULINTAS JL.HR.SOEBRANTAS DUMAI TERHADAP DAMPAK PEMBANGUNAN DUMAI ISLAMIC CENTER - Edria Dianjani; Ari Sandhyavitri; Muhamad Yusa (LPPM Universitas Abdurrab, 2024)
This research aims to identify the performance of the road network in existing conditions on the HR road section. Soebrantas, projected traffic performance in the short term (20238) and medium term (2032) against scenarios used for traffic engineering for DIC development, as well as comparing traffic handling scenarios in the short term (2028) and long term. middle (2032). This research uses primary data in the form of traffic data (2023), Dumai City spatial pattern planning maps. The parameters measured are traffic flow and side obstacles which influence HR road traffic performance. Soebrantas. ResultsThis research shows that side obstacles are the dominant factor that influences traffic flow, resulting in traffic jams or congestion. Scenario 2 is the best strategy that can be used because it is necessary to reduce the occurrence of side obstacles.